EASEMENT: STAGES OF DEVELOPMENT - Abdulkhaeva Anisa Abdumalikovna (TADQIQOTLAR, 2025)
Abstract: In this article, the author examines the legal nature of an easement (the right of limited use of someone else's land). As one of the institutions of civil law. The  stages  of  easement  development  from  well-known  land  forms  to  the  form  of easement in the digital space are studied.  The most important phases of development are regarded: Roman law, the unification of easements in civil laws of the XIX-XX centuries, their adaptation to the realities of the industrial period. Due to the emergence of new regulatory objects in the Internet space, the author pays attention to changes in the  easement  and  easements  of  legal  relations  in  this  environment.  In  the  end, the author's  conclusion  and  suggestions  on  how  to  improve  this  institution  in  modern realities are given.